2018
DOI: 10.1021/acsami.7b17247
|View full text |Cite
|
Sign up to set email alerts
|

Largely Tunable Band Structures of Few-Layer InSe by Uniaxial Strain

Abstract: Because of the strong quantum confinement effect, few-layer γ-InSe exhibits a layer-dependent band gap, spanning the visible and near infrared regions, and thus recently has been drawing tremendous attention. As a two-dimensional material, the mechanical flexibility provides an additional tuning knob for the electronic structures. Here, for the first time, we engineer the band structures of few-layer and bulk-like InSe by uniaxial tensile strain and observe a salient shift of photoluminescence peaks. The shift… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

7
77
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 95 publications
(89 citation statements)
references
References 39 publications
(86 reference statements)
7
77
1
Order By: Relevance
“…We found that the PL peak energies of our as‐grown InSe nanoflakes were comparably lower than those of their exfoliated samples . This difference in PL energy may be attributed to the built‐in tensile strain which arose from the lattice mismatch between InSe and mica . The optical bandgaps of the InSe nanoflakes grown on mica substrate were calculated considering the e–h interaction via the GW method, consistent with the experimental results (Figure S6, Supporting Information).…”
Section: Resultssupporting
confidence: 80%
See 1 more Smart Citation
“…We found that the PL peak energies of our as‐grown InSe nanoflakes were comparably lower than those of their exfoliated samples . This difference in PL energy may be attributed to the built‐in tensile strain which arose from the lattice mismatch between InSe and mica . The optical bandgaps of the InSe nanoflakes grown on mica substrate were calculated considering the e–h interaction via the GW method, consistent with the experimental results (Figure S6, Supporting Information).…”
Section: Resultssupporting
confidence: 80%
“…As the thickness of the InSe nanoflakes decreased from bulk to three layers, the peak energy of PL increased from 1.23 to 1.60 eV (Figure c), while the PL intensity decreased dramatically. We found that the PL peak energies of our as‐grown InSe nanoflakes were comparably lower than those of their exfoliated samples . This difference in PL energy may be attributed to the built‐in tensile strain which arose from the lattice mismatch between InSe and mica .…”
Section: Resultsmentioning
confidence: 72%
“…As a novel layered chalcogenide, InSe has excellent photoelectric properties and a high quantum size limiting effect, with a bandgap that can be controlled with the number of layers. At room temperature, the bandgap of InSe can be increased from 1.26 to 2.11 eV with an increasing number of layers, which indicates that InSe has a broadband light absorption range from visible light to infrared light . According to previous reports, the carrier mobility in InSe nanosheets can reach 423 and 1006 cm 2 V −1 s −1 , respectively, at room temperature and 78 K, which is better than the previously reported phosphorene (275 cm 2 V −1 s −1 ) .…”
Section: Pec‐type Photodetectors Based On 2d Materialsmentioning
confidence: 69%
“…In figure 2 we have shown the ambient pressure XRD pattern of the exfoliated sample and compared with XRD patterns collected at high pressures. All the intense reflection lines at ambient condition are indexed to a hexagonal structure with space group P mmc 6 3 and lattice parameters a=3.288(8) Å, c=12.958(6) Åwith volume=121.36(6) Å 3 and Z=2, which is consistent with the literature [11,19]. In addition a few new peaks are observed in the ambient pattern, which are indicated by the black arrow in the figure 2 and could only be indexed to a triclinic cell.…”
Section: Resultsmentioning
confidence: 99%
“…Introduction of strain has been found to induce electronic structural transition and enhance the electronic properties in TiS 2 and graphene [1,2]. Tuning of optical band gap with strain in layered two-dimensional (2D) InSe has shown it to be a versatile optoelectronic material [3]. In a recent strain engineering work on the MoSe 2 /WSe 2 heterolayers, it has been shown that decreasing the layer distance by application of uniaxial pressure can change the conductance by several orders of magnitude [4].…”
Section: Introductionmentioning
confidence: 99%